Kuota 30% Perempuan di Parlemen: Implementasi dan Efektivitasnya di Indonesia - Fransin Kontu; Stefanes Pesak (Papsel Journal of Humanities and Policy, 2025)
Abstract Women's representation in parliament is an important indicator in realising gender equality and inclusive democracy. To support this, Indonesia has adopted a 30% quota policy for women in legislative candidacy since the 2004 elections. This policy aims to increase women's participation in politics and ensure women's voices are represented in decision-making. However, even though this policy has been implemented, women's representation in parliament is still far from the expected target. In the 2019 elections, women's representation in the People's Representative Council (DPR) only reached 20.5%. This research analyses the implementation and effectiveness of gender quota policies in Indonesia using a qualitative approach. Findings show that the main obstacles to implementing gender quotas include the dominance of patriarchal culture, lack of support from political parties, discrimination against female candidates, and weak supervision and law enforcement. On the other hand, this policy has made a positive contribution in the form of increasing the number of women elected as legislative members, although this contribution is still limited. In conclusion, the effectiveness of the 30% quota policy for women in parliament requires strengthening commitment from various parties, including political parties, society, and election management institutions. Research recommendations include strengthening the capacity of female candidates, increasing supervision of quota implementation, as well as wider outreach about the importance of women's representation in politics. With these steps, it is hoped that gender equality in parliament can be achieved better in the future. Keywords:, women's representation, parliament, politics, Indonesia.